Unraveling the plasticity of translation initiation in prokaryotes: Beyond the invariant Shine-Dalgarno sequence. - Karel Estrada; Alejandro Garciarrubio; Enrique Merino (PLoS ONE, 2024)
Translation initiation in prokaryotes is mainly defined, although not exclusively, by the interaction between the anti-Shine-Dalgarno sequence (antiSD), located at the 3'-terminus of the 16S ribosomal RNA, and a complementary sequence, the ribosome binding site, or Shine-Dalgarno (SD), located upstream of the start codon in prokaryotic mRNAs. The antiSD has a conserved 5'-CCUCC-3' core, but inter-species variations have been found regarding the participation of flanking bases in binding. These variations have been described for certain bacteria and, to a lesser extent, for some archaea. To further analyze these variations, we conducted binding-energy prediction analyses on over 6,400 genomic sequences from both domains. We identified 15 groups of antiSD variants that could be associated with the organisms' phylogenetic origin. Additionally, our findings revealed that certain organisms exhibit variations in the core itself. Importantly, an unaltered core is not necessarily required for the interaction between the 3'-terminus of the rRNA and the region preceding the AUG of the mRNA. In our study, we classified organisms into four distinct categories: i) those possessing a conserved core and demonstrating binding; ii) those with a conserved core but lacking evidence of binding; iii) those exhibiting binding in the absence of a conserved core; and iv) those lacking both a conserved core and evidence of binding. Our results demonstrate the flexibility of organisms in evolving different sequences involved in translation initiation beyond the traditional Shine-Dalgarno sequence. These findings are discussed in terms of the evolution of translation initiation in prokaryotic organisms.